Download BI AV − = IR VV − = B RA V = = , + IR VV − = – Rth Vth Iab

yes no Was this document useful for you?
   Thank you for your participation!

* Your assessment is very important for improving the work of artificial intelligence, which forms the content of this project

Document related concepts

Ohm's law wikipedia, lookup

Switched-mode power supply wikipedia, lookup

Electrical substation wikipedia, lookup

Stray voltage wikipedia, lookup

Alternating current wikipedia, lookup

Mains electricity wikipedia, lookup

Resistive opto-isolator wikipedia, lookup

Islanding wikipedia, lookup

Buck converter wikipedia, lookup

Rectiverter wikipedia, lookup

Current source wikipedia, lookup

Opto-isolator wikipedia, lookup

Network analysis (electrical circuits) wikipedia, lookup

Notes on Thevenin Equivalents. Dr. Mack Grady.
Aug. 28, 2009
The three cases to consider are
• Case 1. All sources are independent
• Case 2. The circuit has dependent sources and independent
• Case 3. The circuit has only dependent sources
Depending on the case, one or more of the following methods can be
used to find the Thevenin equivalent:
Direct Rth. (Applies only to Case 1).
• Turn off all independent sources (i.e., set V = 0 for voltage
sources, and I = 0 for current sources). Note - this is the
same thing as replacing voltage sources with short circuits,
and current sources with open circuits.
• Connect a fictitious ohmmeter across terminals a-b, and
“measure” Rth directly.
• Find Isc (or, alternatively, find Voc = Vth ).
• Compute Vth = Voc = Isc • Rth (or, alternatively, Isc = Voc /
Rth ).
• If time permits, find Vth (or, alternatively, Isc ) directly from
the circuit, and then double-check with the above.
Voc , Isc (Applies to Cases 1 and 2).
• Find Voc = Vth .
• Find Isc .
• Compute Rth = Vth / Isc .
Fictitious Source (Applies to all Cases)
• Attach a fictitious source Vab across terminals a-b. Find a
linear equation with the following form: Vab = A − BI ab .
By definition the linear equation must match Thevenin
equation Vab = Vth − Rth I ab , term by term. Thus,
matching the terms yields Vth = A, Rth = B .
Direct Rth.
Voc , Isc
Case 1
Case 2
Case 3
Vab = Vth − Rth I ab
Note – For Case 3, the Vth should be zero. Thus, for Case 3, you
can attach any voltage source Vab to the output (e.g., Vab = 1V),
find I ab , and compute Rth =
− Vab
I ab